Viruses Previously Identified in Brazil as Belonging to HIV-1 CRF72_BF1 Represent Two Closely Related Circulating Recombinant Forms, One of Which, Designated CRF122_BF1, Is Also Circulating in Spain - Cañada-García, Javier E.; Delgado, Elena; Gil, Horacio; Benito, Sonia; Sánchez, Mónica; Ocampo, Antonio; Cabrera, Jorge Julio; Miralles, Celia; García-Bodas, Elena; Mariño, Ana; Ordóñez, Patricia; Gude, María José; et al. (Frontiers in Microbiology, 2022)
Circulating recombinant forms (CRFs) are important components of the HIV-1 pandemic. Those derived from recombination between subtype B and subsubtype F1, with 18 reported, most of them of South American origin, are among the most diverse. Here we identify a HIV-1 BF1 recombinant cluster that is expanding in Spain, transmitted mainly via heterosexual contact, which, analyzed in near full-length genomes in 4 viruses, exhibited a coincident BF1 mosaic structure, with 12 breakpoints, that fully coincided with that of two viruses from Brazil (10BR_MG003 and 10BR_MG005), previously classified as CRF72_BF1. The three remaining Brazilian viruses previously identified as CRF72_BF1 (10BR_MG002, 10BR_MG004, and 10BR_MG008), exhibited mosaic structures highly similar, but not identical, to that of the Spanish viruses and to 10BR_MG003 and 10BR_MG005, with discrepant subtypes in two short genome segments, located in pol and gp120env. Based on these results, we propose that the 5 viruses from Brazil previously identified as CRF72_BF1 actually belong to two closely related CRFs, one comprising 10BR_MG002, 10BR_MG004, and 10BR_MG008, which keep their CRF72_BF1 designation, and the other, designated CRF122_BF1, comprising 10BR_MG003, 10BR_MG005 and the viruses of the identified Spanish cluster. Three other BF1 recombinant genomes, 2 from Brazil and 1 from Italy, previously identified as unique recombinant forms, were classified as CRF72_BF1. CRF122_BF1, but not CRF72_BF1, was associated with protease L89M substitution, reported to contribute to antiretroviral drug resistance. Phylodynamic analyses estimate the emergence of CRF122_BF1 in Brazil around 1987. Given their close phylogenetic relationship and similar structures, the grouping of CRF72_BF1 and CRF122_BF1 in a CRF family is proposed.